Quantitative Evaluation of the Severity of Acute Illness in Adult Patients with Tick-Borne Encephalitis - Bogovic, Petra; Logar, Mateja; Avsic-Zupanc, Tatjana; Strle, Franc; Lotric-Furlan, Stanka (BioMed research international, 2014)
The aim of the present study was to quantify the severity of acute illness in patients with tick-borne encephalitis and to ascertain this approach by comparing it to standard clinical assessment. We designed scoring system for quantification of the severity of acute illness in patients with tick-borne encephalitis. Certain number of points was allotted to the presence, intensity, and duration of individual symptoms/signs. According to the obtained score the disease was classified as mild, moderate, and severe. Tick-borne encephalitis was assessed clinically as mild when only signs/symptoms of meningeal involvement were found, moderate in case of monofocal neurological signs and/or mild to moderate signs/symptoms of central nervous system dysfunction, and severe in patients with multifocal neurological signs and/or symptoms of severe dysfunction of central nervous system. By designed scoring system 282 adult patients, 146 males and 136 females, average aged 52.2 ± 15.5 years (range 15–82 years), with confirmed tick-borne encephalitis, were prospectively assessed. In 279/282 (98.9%) patients the severity according to clinical assessment matched with the score ranges for mild, moderate, and severe disease. The proposed approach enables precise and straightforward appraisal of the severity of acute illness and could be useful for comparison of findings within/between study groups.